'Key selection criteria' as administrative devices: An investigation of academic bureaucratization at Australian universities. (8th December 2020) - Woelert, Peter
Abstract: Over recent decades, tensions arising from the ways universities operate have become increasingly apparent. While there have been ongoing ambitions to reduce traditional bureaucratic mechanisms and 'red tape' within universities, there has been mounting concern internationally that the administrative dimensions of academic work are becoming increasingly burdensome (a phenomenon also referred to as 'academic bureaucratization'). This article explores how a specific administrative device used at Australian universities—the 'key selection criteria' (KSC) that applicants have to address in writing when applying for academic positions—manifests academic bureaucratization. The analyses of the size, composition, and content of 273 sets of KSC conducted for this article suggest that academic bureaucratization at Australian universities is well entrenched, fueled by the sedimentation of and redundancy in formal elements, and is further reinforced by vacuously-worded requirements reflecting attitudes of indifference, complacency, or cynicism if considering the prospective informational value of applicants' response.